Progress and Prospects of Triazoles in Advanced Therapies for Parasitic Diseases - Jaime A. Isern; Renzo Carlucci; Guillermo R. Labadie; Exequiel O. J. Porta (Tropical Medicine and Infectious Disease)
Parasitic diseases represent a severe global burden, with current treatments often limited by toxicity, drug resistance, and suboptimal efficacy in chronic infections. This review examines the emerging role of triazole-based compounds, originally developed as antifungals, in advanced antiparasitic therapy. Their unique structural properties, particularly those of 1,2,3- and 1,2,4-triazole isomers, facilitate diverse binding interactions and favorable pharmacokinetics. By leveraging innovative synthetic approaches, such as click chemistry (copper-catalyzed azide–alkyne cycloaddition) and structure-based design, researchers have repurposed and optimized triazole scaffolds to target essential parasite pathways, including sterol biosynthesis via CYP51 and other novel enzymatic routes. Preclinical studies in models of Chagas disease, leishmaniasis, malaria, and helminth infections demonstrate that derivatives like posaconazole, ravuconazole, and DSM265 exhibit potent in vitro and in vivo activity, although their primarily static effects have limited their success as monotherapies in chronic cases. Combination strategies and hybrid molecules have demonstrated the potential to enhance efficacy and mitigate drug resistance. Despite challenges in achieving complete parasite clearance and managing potential toxicity, interdisciplinary efforts across medicinal chemistry, parasitology, and clinical research highlight the significant potential of triazoles as components of next-generation, patient-friendly antiparasitic regimens. These findings support the further optimization and clinical evaluation of triazole-based agents to improve treatments for neglected parasitic diseases.